Theather As an Awakening Vaccine (Brechtian Concept) - Warih Witjitra Wening (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2021)
As soon as this article discusses the theateropportunity as anawakening vaccine in Indonesian society during the Covid 19pandemic. Art has become the most powerful medium to reach thepublic area in the middle of a fairly tension and uncertain nationalsituation. This discussion will present Bertolt Brecht concept ofthinking in a different form of thought, but the author believes that inthe social condition that occurs in the middle of Indonesian peoplewho are panicking, theater is the right solution. Brechtian concept hasthe idea that allapparatus of performance, including audiences arerequired to stay apart nowadays, this is a reality that examines artistsand audiences due to physical distancing from the actual theater.Nobody realizes that the concept of verfremdungsefekt which isdefined as isolation, distance, or alienation is now becoming morepowerful in the middle of the pandemic. The basic thinking makes thewriter believe that to create a healthy physical condition, theatervaccineis the answer as awareness both conceptually in performanceand in presentational performance fragment, the author thinks that it isa strategy in the social condition nowadays